Role of oil prices in financial instability, trade openness and economic growth: evidence from Asean countries - Maikudi Muhammad; Ali Umar Ahmad; Aminu Hassan Jakada; Atiku Mohammed Abubakar (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper examined the interaction effect of oil prices on financial instability, trade openness, and economic growth in leading ASEAN countries. Based on the data over 1970-2019, this research used the second-generation panel approach to examine the effects of this study. The results of the cross-sectional dependency (CD) test, and the slope homogeneity test showed that the slope heterogeneity exists among countries and the relationship between cross-sectional units. The findings of the co-integration have showed that financial instability, trade openness, oil prices and economic growth have a stable and long-run linkages. In addition, the findings have shown that economic growth is adversely impacted by financial instability and oil prices, and that trade openness has a positive effect on economic growth. The findings further demonstrated the negative effects on economic growth of the interaction term with oil prices and financial instability. The interaction term for oil prices and openness in trade, however, has a positive effect on leading ASEAN economies' economic growth. Nevertheless, the findings of the causal test showed a one-way causal association between financial instability and economic growth; oil prices and economic growth. Similarly, the results confirmed the bidirectional causality between trade openness and economic growth.